Analysis of the location for peak heating in CHP based combined district heating systems. (5th August 2015) - Wang, Haichao; Lahdelma, Risto; Wang, Xin; Jiao, Wenling; Zhu, Chuanzhi; Zou, Pinghua
Abstract: Combined heat and power (CHP) is the main technology for providing the base load of district heating in China. However, CHP is not efficient for providing the peak load; instead, a peak boiler with high efficiency could be used to compensate the peak load. This paper studies how the location of the peak boiler can affect the energy efficiency and economic performance of such CHP based combined district heating system. Firstly, the connection mode and the control strategy for different peak heating locations are analyzed. Then the effect of the peak boiler's location on the initial investment of the network and the cost for distributing heat is studied. The objective is to place the peak boiler in a location where the overall costs are the smallest. Following this rule, the results indicate that the peak boiler should be located at the CHP plant if that allows using cheaper 'self-use electricity' in CHP for distributing the heat. However, if the market electricity price is used everywhere, or if energy efficiency is more emphasized, the location of the peak boiler should be closer to the users with dense heat loads. Highlights: Location for peak heating in the CHP based combined DH system is studied. Regulation or control strategies for combined DH are summarized. The heat load duration curve for combined DH is demonstrated. Network design for combined DH with peak boiler outside of the CHP is analyzed.